2014
DOI: 10.1063/1.4867399
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, and magnetic properties of (Co, Cu)-codoped ZnO films with different Co concentrations

Abstract: Room temperature ferromagnetic and ultraviolet optical properties of Co-doped ZnO nanocluster films Zn 0.99-x Co x Cu 0.01 O films with different Co concentrations from 0% to 20% were fabricated by a sol-gel method. Moderate Co doping is found to improve the surface uniformity and crystal quality of the films, and causes a redshift of the band edge of Zn(Co,Cu) films. X-ray photoelectron spectroscopy reveals that the introduction of Co ions causes the valence state of Cu to change from þ2 to þ1; while at Co co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
1
10
1
Order By: Relevance
“…As is well known, the redshift of a band edge could be due to the spin-exchange interaction between the sp band and localized spins of transition-metal ions [32]. That is, the exchange interaction between the transition-metal ions and the band electrons, the so-called sp-d interaction, causes negative and positive corrections, respectively, to the conduction and valence band energy, and hence decreases the E g of the films [4].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…As is well known, the redshift of a band edge could be due to the spin-exchange interaction between the sp band and localized spins of transition-metal ions [32]. That is, the exchange interaction between the transition-metal ions and the band electrons, the so-called sp-d interaction, causes negative and positive corrections, respectively, to the conduction and valence band energy, and hence decreases the E g of the films [4].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…few ZnO particles are generated with a large amount of Zn (OH) 4 2-from a sol of low pH value, according to formula (3), accompanied by weak thin film luminescent intensity. One can see that the intensity of the UV peak increases gradually with increasing pH value.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Lin [14] synthesized ZnCoO that exhibited obvious ferromagnetic ordering above room temperature if prepared with a particular amount of Cu doping by a standard solid-state reaction method. Recently, we reported that (Co, Cu)-doped ZnO shows a red-shift compared to the case when either Co or Cu atoms alone are used to dope ZnO [4,15].…”
mentioning
confidence: 96%